Analisis Pola Asuh Orang Tua Terhadap Perkembangan Bahasa Ekspresif Anak usia 5-6 Tahun di Taman Kanak-Kanak Batara Bira - Jihan Nadia; Rusmayadi, Rusmayadi; Hajerah, Hajerah (UNIB Press, 2025)
Expressive language is a crucial aspect of children's communication and socio-emotional development, reflecting their ability to convey ideas, feelings, and needs verbally. This study aims to examine the influence of parenting styles on expressive language development in children. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. Participants included eight children aged 5-6 years, eight parents, and three teachers. Data validity was ensured through source triangulation and methodological triangulation. The findings demonstrate that democratic parenting significantly supports expressive language development, as evidenced by enhanced vocabulary acquisition, improved sentence construction abilities, and increased confidence in verbal expression. Conversely, authoritarian parenting restricts children's expressive abilities, while permissive parenting provides freedom without adequate guidance for language development. Additional factors influencing expressive language development include parental education level, frequency of verbal communication, and parental involvement in children's daily activities. These findings underscore the critical importance of adopting balanced and communicative parenting approaches to foster optimal expressive language development from early childhood.